Germinal Center Kinase–like Kinase Overexpression in T Cells as a Novel Biomarker in Rheumatoid Arthritis. Issue 10 (24th September 2013) - Chen, Yi‐Ming; Chuang, Huai‐Chia; Lin, Wen‐Chun; Tsai, Ching‐Yi; Wu, Chia‐Wei; Gong, Ning‐Rong; Hung, Wei‐Ting; Lan, Tsuo‐Hung; Lan, Joung‐Liang; Tan, Tse‐Hua; Chen, Der‐Yuan
<x xml:space="preserve">Abstract</x> Objective Germinal center kinase–like kinase (GLK; also called MAPKKKK‐3) activates protein kinase Cθ (PKCθ) during T cell activation and controls autoimmunity in lupus patients. Intracellular kinases are involved in the pathogenesis of rheumatoid arthritis (RA). We undertook this study to determine the role of GLK in RA. Methods The severity of collagen‐induced arthritis (CIA) was studied in GLK‐deficient mice. Expression levels of GLK from RA patients were determined by Western blotting, flow cytometry, real‐time polymerase chain reaction, and immunohistochemical staining. Localization of GLK in T cells was identified by confocal microscopy. RA disease activity was assessed using the Disease Activity Score in 28 joints. Results GLK‐deficient mice displayed impaired CIA development and decreased inflammatory cytokine levels. Local T cell infiltration and collagen restimulation responses were impaired by GLK deficiency. RA patients showed significantly higher GLK protein and messenger RNA levels in peripheral blood T cells than did healthy controls. GLK‐overexpressing T cells in synovial fluid and synovial tissue samples from RA patients were increased compared with those from osteoarthritis patients. Confocal microscopy and flow cytometry showed that GLK colocalized and coexisted with phosphorylated PKCθ in T cells from RA patients. Frequencies of GLK‐expressing T cells were significantly correlated with RA disease activity. Conclusion GLK overexpression in T cells contributes to the pathogenesis of RA, indicating that GLK is a novel biomarker for autoimmune disease severity and a potential therapeutic target for RA.